An Analysis of the “Barbiecore” Fashion Trend from a PR Marketing Perspective - Nila Nurlimah; Indriyati Kamil; Raihan Reynaldi (CV Edujavare Publishing, 2026)
An Analysis of the “Barbiecore” Fashion Trend from a PR Marketing Perspective